FORMATION OF PROFESSIONAL COMPETENCIES OF THE FUTURE TEACHERS BY MEANS OF A COMPUTER-BASED METHODOLOGY: INVESTIGATIONAL APPROACH - Valentyna I. Bobryts’ka; Svitlana M. Prots’ka (Інформаційні технології і засоби навчання, 2018)
The article validates feasibility of the investigational research of the problem of formation of the future teachers’ professional competencies by means of a computer-based methodology; it determines the author’s approach to the interpretation of the essence of the computer-based methodology for the formation of professional competencies of the future teachers; it specifies the structural components of the computer-based methodology of formation of professional competencies of the future teachers: goals (objectives) of learning, content of learning, forms of educational process organisation, methods and tools of learning; it specifies the most effective traditional and computer-based forms, methods and tools of learning of Pedagogical disciplines for the students obtaining a Bachelor’s degree. This article discusses the interconnectedness of open source education and tools of the computer-based methodology for the formation of professional competencies of the future teachers; it reveals the structural components of professional competencies (subject-learned area, information and digital, communicative, personality, creativity) of the future teachers; works out the criteria (motivation-based and goal-setting, professional and cognitive, vocational and cognitive, reflexive and evaluational components), indicators, and levels (based on the analysis level, elementary (reproductive) level, creative (advanced) level) of formation of professional competencies of the future teachers in the settings of educational process at higher education institutions; highlights a complex of general scientific theoretical, empirical and statistical methods and consolidated results of a pedagogical investigation (analytics and search, experimental (ascertaining and formative) and bottom-line and correctional stages) on the study of the problem of the formation of professional competencies of the future teachers by means of the computer-based methodology in the settings of learning the disciplines of Pedagogy.